189k views
1 vote
X^2-4x+3 factorize into its factors and give me answer I will giv u anda burger

User Krystal
by
5.4k points

2 Answers

4 votes

Answer:

(x - 3)(x - 1)

Explanation:

Consider the factors of the constant term (+ 3) which sum to give the coefficient of the x- term.

The factors are - 3 and - 1, since

- 3 × - 1 = + 3 and - 3 - 1 = - 4, hence

x² - 4x + 3 = (x - 3)(x - 1) ← in factored form

User Imns
by
5.0k points
3 votes

Answer:

Factors are (x-1) (x-3)

Explanation:

X^2-4x+3 = 0

x² - x - 3x + 3 =0

x(x - 1) -3(x - 1) = 0

(x-1) (x-3) =0

User Wiomoc
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.